Acute inflammation in horizontal incompletely impacted third molar with radiolucency in the elderly - Minoru Yamaoka (Dove Medical Press, 2009)
Minoru Yamaoka, Yusuke Ono, Masahiro Takahashi, Masahide Ishizuka, Takayuki Uchihashi, Kouichi Yasuda, Takashi Uematsu, Kiyofumi FurusawaMatsumoto Dental University, Oral and Maxillofacial Surgery, Shiojiri, Nagano, JapanAbstract: Although radiolucency has been shown as a risk of infection, the poorly understood effects of aging on radiolucency correlate with acute pericoronitis, which has a high risk of infection extending any complications. We reviewed the records of 346 consecutive patients aged more than 41 years to evaluate whether pericoronal radiolucency below the crown in mandibular horizontal incompletely impacted third molars is related to acute inflammation. The frequency of acute inflammation in teeth with pericoronal radiolucency below the crown was similar to that in teeth without; however, the odds ratio of acute inflammation exhibited in women aged more than 61 years compared to women aged 41–50 years was 9.77 (95% confidence interval [CI]: 1.67–57.29; P <<0.05), and in women aged more than 61 years compared to women aged 51–60 years was 26.25 (95% CI: 2.94–234.38; P < 0.01). The odds ratio of severe acute inflammation exhibited in men aged more than 61 years compared to men aged 41–50 years was 16.67 (95% CI: 1.76–158.27; P < 0.01). These odds ratios indicate an association of acute pericoronitis, including the severe forms of acute inflammation that result from pericoronitis, with pericoronal radiolucency below the crown in the elderly.Keywords: radiolucency, mandible, third molar, acute inflammation, aging